Digital Footprints and Field Observations: A study on Cirebon's traditional culinary landscape - Gitasiswhara; Millary Agung Widiawaty; Moh. Dede; Ahmad Hudaiby Galih Kusumah (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2026)
This study aims to analyze consumer perceptions of Cirebon's traditional cuisine by integrating online review data and direct field observations. The research method uses a mixed-method approach on 13 sample eateries, combining web scraping for sentiment analysis of text reviews from Google Maps (January to June of 2025) and structured observation to assess parameters such as taste, facilities, service, price, and location. The research also employs Spearman's analysis to examine relationships between variables. The results reveal a popularity-quality paradox, where digital popularity (number of reviews) does not always linearly correlate with high ratings; eateries with few reviews often achieve very high ratings due to quality consistency and a holistic dining experience. Our study indicates that Google Maps ratings are most strongly influenced by perceived value for money and the atmosphere of the eatery. We confirm that while there is general alignment between online reviews and on-ground reality, consumer assessments on digital platforms are a complex construct influenced by holistic experiential factors beyond just the food taste. Integrating direct observations with online reviews comprehensively reveals factors shaping consumer satisfaction in local culinary tourism.